A critical review of methotrexate clinical interactions: role of transporters. (1st February 2023) - Jafari, Fatemeh; Arasteh, Omid; Hosseinjani, Hesamoddin; Allahyari, Abolghasem; Ataei Azimi, Sajad; Askari, Vahid Reza
ABSTRACT: Introduction: Methotrexate (MTX) is an antifolate and immunosuppressive drug prescribed for various malignancies and immune diseases. However, delayed elimination of MTX associated with concomitant use of some medications can lead to severe and lifethreatening adverse effects. Areas covered: This paper investigated drugMTX interactions that lead to elevated MTX levels and related adverse effects due to the role of transporters. Methotrexate toxicity occurs at both low and high doses administrations. According to the studies we reviewed in this paper, most interaction records with methotrexate occurred with coadministration of indomethacin, ketoprofen, omeprazole, piperacillin/tazobactam, ciprofloxacin, cotrimoxazole, probenecid, and imatinib, mainly due to the role of transporters. However, most studies were performed as case reports or series, and confirming the exact drugmethotrexate interaction still needs further clinical investigations. Expert opinion: Our findings showed no firm evidence of interactions of proton pump inhibitors (PPIs), levetiracetam, and NSAIDS with MTX. Moreover, patients' risk factors, hypoalbuminemia, renal failure, third space fluid retention, the elderly, polypharmacy, and transport inhibition are the most critical factors for MTX toxicity. If substitution or temporary discontinuation is not possible, healthcare providers should be aware of interactions, especially in patients with risk factors for MTX toxicity.